The effects of changes in flowering plant composition caused by nitrogen and phosphorus enrichment on plant–pollinator interactions in a Tibetan alpine grassland - Wang, Lin-Lin; Ren, Fei; Zhang, Chan; Huang, Xiao-Juan; Zhang, Zhen-Hua; He, Jin-Sheng; Yang, Yong-Ping; Duan, Yuan-Wen (Frontiers in Plant Science, 2022)
Soil eutrophication from atmospheric deposition and fertilization threatens biodiversity and the functioning of terrestrial ecosystems worldwide. Increases in soil nitrogen (N) and phosphorus (P) content can alter the biomass and structure of plant communities in grassland ecosystems; however, the impact of these changes on plant–pollinator interactions is not yet clear. In this study, we tested how changes in flowering plant diversity and composition due to N and P enrichment affected pollinator communities and pollination interactions. Our experiments, conducted in a Tibetan alpine grassland, included four fertilization treatments: N (10 g N m-2 year-1), P (5 g P m-2 year-1), a combination of N and P (N + P), and control. We found that changes in flowering plant composition and diversity under the N and P treatments did not alter the pollinator richness or abundance. The N and P treatments also had limited effects on the plant–pollinator interactions, including the interaction numbers, visit numbers, plant and pollinator species dissimilarity, plant–pollinator interaction dissimilarity, average number of pollinator species attracted by each plant species (vulnerability), and average number of plant species visited by each pollinator species (generality). However, the N + P treatment increased the species and interaction dissimilarity in flowering plant and pollinator communities and decreased the generality in plant–pollinator interactions. These data highlight that changes in flowering plants caused by N + P enrichment alter pollination interactions between flowering plants and pollinators. Owing to changes in flowering plant communities, the plant–pollinator interactions could be sensitive to the changing environment in alpine regions.